Changes of body composition among university students depending on the consumption frequency of selected bakery products - Martina Gažarová; Lucia Mečiarová; Silvia Meňhartová; Maroš Bihari (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Bakery products such as bread, rolls, croissants and others are an important part of eating habits. Recently, their consumption has been associated with an undesirable increase and prevalence of overweight or obesity. Objective. The aim of the work was to analyze the influence of the consumption frequency of selected types of bread / bakery products on anthropometric parameters in a group of university students. Material and Methods. The group was composed of 120 volunteers consuming different types of bread / bakery products with different consumption frequencies during the week. The anthropometric parameters were measured by InBody 720. To obtain information on the frequency of consumption we used the questionnaire method. Results. The results suggest that in most cases it is not the type of product that is decisive, but its quantity consumed and frequency of consumption supported by low daily physical activity, resp. sedentary lifestyle. We found similar results of the influence of the consumption frequency on anthropometric parameters for all types of bread. Low levels of physical activity, basal metabolism and consumption of selected types of bakery products (wheat bread, wheat rolls, sweet pastries and gluten-free variants) can cause an increase in visceral as well as total body fat, weight gain, BMI, at the expense of fat-free mass. Our results showed that the groups of participants who did not consume a certain type of bread at all, rarely or 1 to 3 times a week, showed higher values of the examined parameters (BMI, body weight, body fat percentage, WHR) compared to the group which consumed a particular type of bakery products on average 4 to 7 times a week. The parameter´s values were largely influenced by the levels of physical activity. Conclusions. Based on the results it is possible to assume that if the bakery products are the part of a balanced diet with regard to the individual energy needs, it should not be the main cause of overweight / obesity in humans.